KERAGAAN EKSISTING TANAMAN AREN (Arenga pinnata Merr) DI SUMATERA UTARA (Peluang dan Potensi Pengembangannya) - Lukas Sebayang (Talenta Publisher, 2016)
Sugar palm (Arenga pinnata, Merr) is the most important after the coconut because it is a versatile crop that has the potential to be developed. Sugar palm main products are produced from extracting male flower it can be made as sugar, drinks, acetic and alcohol. Other parts of the plant can be use for ingredient. Data from 2004 shows sugar palm plantation covers 5288.91 acres that are spread in 20 districts in North Sumatra. Utilization sugar palm excellent for especially extracting products can be used as feedstock for ethanol as the needs of the bioenergy development will need to be followed up. Opportunities and potential development in North Sumatra palm is huge in because ecosystems, climate and suitability of land in this area is very suitable for the sugar plant . Opportunities and potential development sugar palm in North Sumatra is very large in because ecosystems, climate and suitability of land in this area is very suitable for the sugar palm plant. Besides adaptable to various types of soils including degraded lands , reeds and for reforestation and forest conservation . Data in 2014 , there is the land area is temporarily not cultivated in North Sumatra tend to rise until 2013, covering an area of 296 032 ha . Another challenge than land development , are super - impose intesifikasi input technology is still minimal , improvement of production management , improved processing , marketing is still traditional , dissemination is still limited to a small proportion of farmers , and the difficulty of seeds . So, we need a shared commitment between the central government and local governments to create policies how the potential development of the sugar plant can be followed in the future. This paper reviews the prospects of development potential, especially palm acreage potential, opportunities and challenges as well as the availability of the technology in North Sumatra.